Hardware Realization of Long Range (LoRa) Based Telemetry System for Aquaculture Monitoring - Bagas Prasetyo; Purno Tri Aji (Universitas Negeri Yogyakarta, 2023)
Freshwater fish farming must pay attention to the condition of the water content in the pond and the water quality in the pond. Fish will feel comfortable if the efficiency of oxygen levels and pond water content is maintained. Freshwater fish farming needs to optimize crop yields so as not to get losses. The problem that is often encountered is that many fish die in the pond due to lack of water. Irrigation channels leading to fishponds experience blockages. The smoothness of the irrigation channel affects the volume of water in the pond. Blockage of irrigation channels is usually due to garbage trapped in irrigation, causing dirty water to settle and water sequestration to occur in the pond. This tool system aims to improve water quality and increase the efficiency of oxygen levels by using TDS and ultrasonic sensors. The parameter value on the sensor affects the work of the tool actuator. The tool actuator is a water pump that is used as a substitute for irrigation channels and an aerator motor to increase dissolved oxygen in water by moving the propeller on the surface of the pond water. Wireless technology is used for data communication. Because the land of freshwater fish farming ponds is a large area and is far from settlements, wireless communication is suitable for enabling easy and fast access to information and services. In this research, the testing methods used are functional testing and system performance testing. Functional testing is used to prove whether the system that has been implemented can meet the requirements of operational functions as planned. System performance testing is intended to monitor several parameters that can show the ability and reliability of the system in carrying out its operational functions. The result of the overall test is the LoRa communication distance that can communicate up to about 1000 meters, proving that LoRa technology has a strong enough ability in terms of range wireless communication. The PLE (Path Loss Exponent) of the LoRa module with 100 meters in LoS (indoor) conditions is 7.77, while in nLoS conditions in obstructed in-building, it is 10.13. The average error of the ultrasonic sensor type JSN SR-04T is 0.16% and has a difference of ± 1 cm. The TDS sensor with dissolved pool water content has an average value of 142.6 ppm with an error value of 1.05%. The PDAM water content has an average value of 112.1 ppm with a sensor value of 1.38%. The water content of the lime and detergent mixture has the highest observed ppm value, which is an average of 737.33 ppm, with a sensor error of 0.14%. The water pump activates when the pool water is low (when the ultrasonic distance reaches 60 cm), and the aerator activates when the water content is contaminated (when the TDS sensor value exceeds 500 ppm).